Efficacy of extractives from parts of Ghanaian pawpaw, avocado and neem on the durability of alstonia - Akwasi Asamoah; Acheampong Atta-Boateng; Kwasi Frimpong-Mensah; Charles Antwi-Boasiako (African Journal of Environmental Economics and Management, 2020)
Conventional preservatives are not only toxic to wood bio-deteriorators, but also to humans and animals. In an effort to find preservatives that are non-toxic to humans and animals, efficacy of water extracts of heartwood of Azadirachta indica (Neem) and leaves of Persea americana (avocado) and Carica papaya (pawpaw) at 0.24%, was tested on the durability of wood of Alstonia boonei by pressure impregnation and buried in a termite-prone field for 5 weeks following a modified EN 252 and Gay et al. (1957). Efficacy was tested on the basis of visual durability ratings, percentage hardness and mass losses of impregnated alstonia wood after burial. Though alstonia wood retained pawpaw extract least, pawpaw extract improved the durability of alstonia wood most. Pawpaw extract could be used to improve the durability of alstonia wood better at 0.72% (3x0.24%) and on triple treatment. 83% of Anloga furniture makers who saw the efficacy of pawpaw extract at 0.72% and on triple treatment, showed a high sense of interest in preservative botanical extracts.